How is the coup impacting science and scientists in Sudan? - Siddig, Ahmed; Ellison, Aaron (My University, 2022)
Military coups (MCs) continue to occur in developing countries with alarming frequency; the current coup in Sudan being the most recent. Regardless of the arguments and rationales behind coups, there is a wide global consensus that coups pose devastating threats to the countries’ development and surrounding regions. In this short essay, we report our own view on the impacts and consequences of the current military crackdown in Sudan and its effects on scientists of Sudan. We conclude with some thoughts for the future. A particular emphasis is on the impacts of the ongoing internet blockade on Sudanese students and researchers, and its long-term and large-scale effects on their ability to build successful academic careers.
Keywords: coup d'etat; Internet; Sudan